Incorporation, Plurality, and the Incorporation of Plurals: a Dynamic Approach - Donka F. Farkas (Universitat Autònoma de Barcelona, 2004)
This paper deals with the semantic properties of incorporated nominals that are present at clausal syntax. Such nominals exhibit a complex cluster of semantic properties, ranging from argument structure, scope, and number to discourse transparency. We develop an analysis of incorporation in the framework of Discourse Representation Theory, a dynamic theory that can connect sentence-level and discourse-level semantics. We concentrate on data from Hungarian, where incorporated nominals may be either morphologically singular or plural. We set out to capture two sets of contrasts: (i) those we find when comparing incorporated nominals on the one hand and their non-incorporated, full-fledged argument sisters on the other, and (ii) those we find when comparing morphologically singular and morphologically plural incorporated nominals. A more elaborate version of the analysis can be found in Farkas and de Swart (2003).